2007
DOI: 10.1007/s10038-007-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCF7L2 polymorphisms with susceptibility to type 2 diabetes in 4,087 Japanese subjects

Abstract: Transcription factor 7-like 2 (TCF7L2) has been shown to be associated with type 2 diabetes mellitus in multiple ethnic groups. Regarding the Asian population, Horikoshi et al. (Diabetologia 50:747-751, 2007) and Hayashi et al. (Diabetologia 50:980-984, 2007) reported that single nucleotide polymorphisms (SNPs) in TCF7L2 were associated with type 2 diabetes in the Japanese population, while contradictory results were reported for Han Chinese populations. The aim of this study was to investigate the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 18 publications
4
51
3
Order By: Relevance
“…There is sufficient evidence of the associations of KCNQ1 and TCF7L2 genes with diabetes as supported by replication studies in the Japanese population. 6,15,27 In addition, SLC30A8, HHEX, CDKN2A/B, IGF2BP2 and CDKAL1 associated with the disease in the European population were found in our earlier study to be associated with the disease in the Japanese population as well. [7][8][9] To further extract genes with strong evidence of the association with diabetes, we attempted to replicate the associations reported earlier using our own data (analysis panel with 2424 cases and 2424 controls).…”
Section: Selection Of Polymorphisms For the Prediction Modelsupporting
confidence: 50%
See 2 more Smart Citations
“…There is sufficient evidence of the associations of KCNQ1 and TCF7L2 genes with diabetes as supported by replication studies in the Japanese population. 6,15,27 In addition, SLC30A8, HHEX, CDKN2A/B, IGF2BP2 and CDKAL1 associated with the disease in the European population were found in our earlier study to be associated with the disease in the Japanese population as well. [7][8][9] To further extract genes with strong evidence of the association with diabetes, we attempted to replicate the associations reported earlier using our own data (analysis panel with 2424 cases and 2424 controls).…”
Section: Selection Of Polymorphisms For the Prediction Modelsupporting
confidence: 50%
“…[1][2][3][4][5] TCF7L2, CDKAL1, CDKN2A/B, IGF2BP2, SLC30A8 and HHEX have been widely replicated as susceptibility genes for type 2 diabetes in Asian populations [6][7][8][9][10][11][12] as well as in populations of European ancestry. 13,14 We recently identified KCNQ1 as a novel susceptibility gene, as well as seven other candidate susceptibility loci in a multistage GWAS for type 2 diabetes in the Japanese population, in which a total of 1612 cases and 1424 controls and 100 000 single nucleotide polymorphisms (SNPs) were included.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to rs7903146 [56], a different downstream variant in the same gene seems to increase diabetes risk in Asians [57]. TCF4 (the protein product of TCF7L2) belongs to a family of transcription factors that contain high mobility group box DNA-binding domains; it binds β catenin after Wnt activation of its receptor, and this transcriptional complex induces the expression of TCF4 target genes.…”
Section: Kcnj11: From Mendelian To Common Disease and Backmentioning
confidence: 99%
“…In 2006, Grant et al [8] identified a microsatellite DG10S478 within intron 3 of TCF7L2 that was associated with type 2 diabetes in an Icelandic, Danish and US cohort. Further studies focused on five single nucleotide polymorphisms (SNPs) (rs12255372, rs7903146, rs7901695, rs11196205 and rs7895340) of TCF7L2 were conducted on different ethnicities [9][10][11][12][13][14][15] and showed strong association between T2DM and TCF7L2 (Table 1).…”
Section: Introductionmentioning
confidence: 99%